KONFLIK NINIK MAMAK DI KENAGARIAN KOTO TUO KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Reni Gusnita; M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated when M.Rasyid holds a Datuok Malintang , is where there is a conflict , each faction seized power among the descendants of Abdul Hadi Datuok Shoots ( Datuok Malintang ) with backrest Datuok Malintang Yahya camp . Though clearly Abdul Hadi who has been crowned the Datuok Malintang , while John was never crowned as Datuok Malintang and never too kua baewik , dagiong bacoca , while many witnesses still alive who saw when Abdul Hadi crowned Datuok Malintang . However ninik mamak Koto Tuo no longer much has changed in favor of the truth , no longer has the properties of a penghoeloe / ninik Mamak , no longer obey customary laws , similar to its already starvin+g wolf where there are many foods that they run and do not care background of children 's nephew , M. Rashid died in 2011 . before he died he had given a mandate to all prince / ninik mamak , that in writing , he reads mandate " during my life , I have submitted all the positions that I hold to my sister Sohibul Manzum " But being backrest shoots Hamdani and his group considers Hamdani who must hold a Dt . Malintang considering his education and his position as a sub-district in District XIII Koto Kampar . With this degree Hamdani and his group can dominate and set the village of Koto Tuo both society and the economy .Key Note : Ninik Mamak Conflicts, Power and Indigenous Matrilineal